Software para Determinar el Patrón de Radiación de Bocinas Cónicas Lisas - Pérez Alfonso, Rafael; Jiménez Hernández, Roberto (Ingeniería, 2001)
A theoretical analysis to determine the radiation pattern for smooth-walled conical horns with inner spherical-wave fronts is presented here. The results obtained with the proposed software are compared to the internationally reported measured values for horns of varied aperture phase errors.